Archie's Superteens - Flynn, Ian, 1982-; Williams, David (Comic book artist); Martin, Gary, 1956-; Doyle, Frank, 1917-1996 (Archie Comic Publications, Inc., 2019)
Presents a collection of graphic novel stories in which Archie, Betty, Veronica, and Jughead transform into their superhero alter egos and save Riverdale from a variety of evil-doers.